Improving complex kinship analyses with additional STR loci. Issue 21 (8th October 2014) - Carboni, Ilaria; Iozzi, Sara; Nutini, Anna Lucia; Torricelli, Francesca; Ricci, Ugo; McCord, Bruce
<x xml:space="preserve">Abstract</x> In a standard paternity testing, mother, child, and alleged father are analyzed with STR markers using commercially available kits. Since Italian civil legislation does not have thresholds to confirm a paternity, paternity is practically proven when likelihood ratio increases prior probability of paternity to posterior, accepted by court as sufficient. However, in some cases the number of markers included in a commercial kit may be insufficient to conclusively prove or disprove a relationship between individuals, especially when complex family scenarios are suspected or indirect analyses are required. Additional genetic information can increase the values of the likelihood ratio regarding the detection of true parental relationships in a pedigree, while reducing the chances of false attributions (e.g. false paternities). In these cases the introduction of a 26Plex amplification system allows to examine 23–26 additional markers depending on the commercial kit used, thus increasing the statistical power of the kinship analysis. The PCR conditions were optimized for a multiplex amplification system and a new generation CE instrument. In order to demonstrate the utility of additional STRs markers, four complex kinship cases are presented.